Optimized lesion size index (o‐LSI): A novel predictor for sufficient ablation of pulmonary vein isolation. Issue 3 (7th April 2021) - Matsuura, Gen; Kishihara, Jun; Fukaya, Hidehira; Oikawa, Jun; Ishizue, Naruya; Saito, Daiki; Sato, Tetsuro; Arakawa, Yuki; Kobayashi, Shuhei; Shirakawa, Yuki; Nishinarita, Ryo; Horiguchi, Ai; et al.
Abstract: Background: Although the lesion size index (LSI) has been well established, it is sometimes difficult to achieve first‐pass pulmonary vein isolation (PVI) and to avoid acute pulmonary vein reconnections, even with LSI‐guided procedures. The purpose of this study was to assess the predictive accuracy of a novel parameter, the optimized lesion size index (o‐LSI), to perform PVI. Methods: The voltage maps created by the Advisor™ high‐density (HD) grid catheter before PVI in 35 atrial fibrillation (AF) patients were examined for an association between the voltage amplitude and insufficient ablation sites (IAS), which were defined as either (i) spontaneous reconnection sites, (ii) dormant PV conduction sites unmasked with 20 mg of adenosine triphosphate disodium hydrate (ATP) injection, or (iii) PV‐LA gap sites after the initial PVI. Results: IAS was observed in 25/1417 of the total ablation sites. IAS was significantly associated with higher bipolar voltage areas (4.20 ± 2.68 vs 2.43 ± 1.93 mV, P < .0001) but not with LSI. A novel index, o‐LSI (defined as LSI/bipolar voltage), was significantly lower in IAS than in others (1.14 [0.82, 1.81] vs 2.35 [1.31, 4.80] LSI/mV). By receiver operating characteristic analysis, an o‐LSI of 2.04 was the best cutoff value for the prediction of IAS (88% sensitivity and 55% specificity, P < .0001, areas under the curve: 0.742). Conclusion: Low o‐LSI was strongly associated with IAS, potentially providing a novel index to improve first‐pass PV isolation. Abstract : To achieve first‐pass pulmonary vein isolation (PVI) and to avoid the acute pulmonary vein reconnections is sometimes difficult even with the lesion size index (LSI)‐guided radiofrequency ablation. We focused on the relationship between the optimized ‐LSI (o‐LSI) (LSI/bipolar voltage within the PV‐encircling lines, which were defined by the Advisor™ HD Grid catheter) and the sufficient ablation sites and found that was strongly associated with acute PV reconnection. The o‐LSI may potentially be novel strategies for durable PVI.